2011
DOI: 10.1002/art.33316
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of vascular homeostasis in patients with Kawasaki disease: Involvement of vascular endothelial growth factor and angiopoietins

Abstract: Objective. In Kawasaki disease (KD), a pediatric vasculitis of medium-sized arteries, the coronary arteries are most commonly affected. Angiopoietins and vascular endothelial growth factor (VEGF) play an important role in maintaining vascular homeostasis. Recently, we identified ANGPT1 and VEGFA as susceptibility loci for KD. This study was undertaken to fine-map these associations and to gain further insight into their role in this vasculitis of unknown etiology to further the search for improved diagnostic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 43 publications
1
18
1
Order By: Relevance
“…The TNF‐α G allele at ‐308 has shown association with increased KD prevalence in several separate studies and also in a systematic review . However, our study failed to demonstrate such association in an Iranian population.…”
Section: Discussioncontrasting
confidence: 81%
“…The TNF‐α G allele at ‐308 has shown association with increased KD prevalence in several separate studies and also in a systematic review . However, our study failed to demonstrate such association in an Iranian population.…”
Section: Discussioncontrasting
confidence: 81%
“…Wang et al reported that serum Th1 and Th2 cytokine expression were higher in KD patients with coronary artery lesions (CALs) than those without CALs [26]. Breunis et al hypothesized that genetic variation may be involved in the development of CALs [27]. Another study revealed that peripheral blood mononuclear cell miR-93 may regulate the expression of vascular endothelial growth factor A and is involved in the pathogenesis of arteritis in acute KD [28].…”
Section: Discussionmentioning
confidence: 99%
“…VEGFA , KDR and ANGPT1 have also been reported to be associated with KD. These data suggest that dysregulation of vascular endothelial growth factor (VEGF) and angiopoietins contributes to the disruption of vascular homeostasis in KD .…”
Section: Kd Aetiologymentioning
confidence: 99%